2013
DOI: 10.5352/jls.2013.23.9.1147
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidation Effect of Leg Bone Extracts and Enzyme Hydrolysates from Jeju Crossbred Horses (Jeju Native Horse×Thoroughbred)

Abstract: This study was conducted to evaluate the antioxidation activity of Jeju crossbred horse (Jeju native horse × thoroughbred) leg bone extracts (HLBE) and its enzyme hydrolysates by determination of 1,1-diphenyl-2picryl-hydrazyl (DPPH), 2,2-azino-bis(3-ethylbenzo thiazoline-6-sulfonic acid) diammonium salt (ABTS) radical scavenging activity, ferric reducing/antioxidant power (FRAP), and oxygen radical absorbance capacity (ORAC). HLBE was extracted with hot water for 24 hr and lyophilized. The lyophilized HLBE was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…5 ). Similar results were reported by Kim et al . (2013) who found that the ORAC activity of pig skin gelatin hydrolysates increased with dose, and 1 mg/mL of pig skin gelatin hydrolysates had 141.39 μM TE/g of ORAC activity.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…5 ). Similar results were reported by Kim et al . (2013) who found that the ORAC activity of pig skin gelatin hydrolysates increased with dose, and 1 mg/mL of pig skin gelatin hydrolysates had 141.39 μM TE/g of ORAC activity.…”
Section: Resultssupporting
confidence: 93%
“…LMP from JHLB significantly reduced ABTS radicals in a dose dependent manner at concentrations ranging from 0.1 to 15 mg/mL. 15 and 20 mg/mL of LMP from JHLB also had ABTS radical scavenging effects that are equivalent to 100 μg/mL of vitamin C. Similarly, Kim et al . (2013) reported that Jeju horse hydrolysates (less than 3 kDa) generated by pepsin and pancreatin hydrolysis showed 0.48 mM TE of ABTS radical scavenging activity.…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations